2008
DOI: 10.1109/tuffc.2008.852
|View full text |Cite
|
Sign up to set email alerts
|

A thickness mode acoustic wave sensor for measuring interface stiffness between two elastic materials

Abstract: We studied thickness vibration of 2 elastic layers with an elastic interface mounted on a plate piezoelectric resonator. The effect of the interface elasticity on resonant frequencies was examined. The result obtained suggests an acoustic wave sensor for measuring the elastic property of an interface between 2 materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Fan et al [4] investigated the Love waves propagating in a metal or dielectric layer/piezoelectric half structure with an imperfect interface and concluded that the imperfection of the interface reduces the phase velocity. Motivated by Refs [3][4][5], Chen et al [6] presented a theoretical model for acoustic wave interface elasticity sensor and indicated that such a sensor can be used to measure the interface properties between two materials.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [4] investigated the Love waves propagating in a metal or dielectric layer/piezoelectric half structure with an imperfect interface and concluded that the imperfection of the interface reduces the phase velocity. Motivated by Refs [3][4][5], Chen et al [6] presented a theoretical model for acoustic wave interface elasticity sensor and indicated that such a sensor can be used to measure the interface properties between two materials.…”
Section: Introductionmentioning
confidence: 99%